Obstacles and factors of non-mosque young people's connection with the mosque - mohammad javad valizadeh (Religion & Communication, 2023)
This research sought to identify the obstacles of non-mosque youths' communication with the mosque. The goal was to find non-mosque youths beyond the mosque youth who have a close and close relationship with the mosque, in order to remove and correct obstacles and strengthen and promote positive factors, to establish and increase the non-mosque youth's relationship with the mosque.This study was applied in terms of purpose and quantitative in terms of execution method. The research population was young people aged 15 to 29 years old in Tehran, and the probability sampling and clustering method was used. The research tool was a questionnaire with a total of 31 questions. The validity of the questionnaire was confirmed using the "preliminary test" and Cronbach's alpha was used to calculate the reliability.The research indicates the existence of fourteen obstacles (prioritized by Fareed Man's table) and three positive and effective factors regarding the connection of young people with the mosque. According to Friedman's ranking of the factors "dry or insincere behavior of the imam of the congregation and the worshipers with the youth", "the presence of the imams of the congregation unattractive to the youth (in terms of morals and behavior)" and "the presence of moral injuries and anomalies among the youth". According to the respondents, the most important obstacles to the connection of non-mosque youths with the mosque are.The findings are consistent with the findings of previous researches, and the effect of the mosque's functions not fitting with the current needs of the people as the reasons for the silence of the mosques, as well as the effect of activity programs, honoring teenagers and young people, giving responsibility and encouragement, in increasing the communication of young people with approves the mosque.